THE CONSTRUCTION OF SELF-IMAGE OF THE SUBJECT OF POST-NATIVE CULTURE FROM THE PERSPECTIVE OF EMOTIONAL BEHAVIOR CHANGE - Liu, Xiaodan; Xia, Huiwen; Ma, Tao; Dang, Qi (International Journal of Neuropsychopharmacology, 2022)
Abstract Background “Houtu” is the most unique cultural symbol and emotional link in the inheritance of agricultural cultural beliefs in ancient China, and it is also one of the important components of contemporary folk culture. Belief has been a unique psychological phenomenon of human beings since ancient times. It reflects human belief and compliance with the world outlook, outlook on life and values through psychological activities. “Houtu belief” originated from people's worship of land and first appeared in ancient agricultural society. Shanxi fenyin is the birthplace of “Houtu belief”, which is regarded as “the oldest ancestor and the most outstanding God in China”. Its temple is also a place for emperors of each dynasty to make pilgrimages and worship gods. It is also regarded as the crown of Houtu temple in China and the source of Houtu Royal worship. At the same time, with the rise of the study of regional emotional change, this study also helps to better understand the later beliefs. Subjects and Methods Starting with the investigation of Houtu temple in fenyin County, Shanxi Province, this paper puts forward some problems, such as divine gender, image transformation and so on. From the pre Qin Dynasty to the early Western Han Dynasty, the Houtu God was the God of men, but now the Nuwa statue in Wanrong Houtu temple is the God of women. What's the reason? In view of this, this paper examines the evolution process and function of backland image from the perspective of belief psychology, and probes into its contemporary artistic value. In addition, this paper also uses Likert scoring method to evaluate the scale. Pearson correlation, standard deviation and statistical significance are combined to illustrate the correlation. The t-test of independent samples was used to verify the differences between male and female believers. According to the statistical value of emotion, participants were divided into three groups: low, medium and high groups. The questionnaire includes two kinds of anxiety, namely debilitating emotion and promoting emotion. Through t-test, univariate and multivariate analysis of variance and regression analysis, we investigated the relationship between time span, psychological activities and social status of believers of different beliefs and genders. Results According to the conclusion of this paper, the evolution of Houtu culture is an interactive process between objective social environment and subjective belief psychology. The image of Houtu culture and its belief activities have experienced a relatively unique cultural evolution process. The study studied male god believers and goddess believers, and found that compared with male god believers, goddess believers have much higher social status and audience. However, there was no significant difference in emotional level between male and female gods. With the development of society, it is gradually socialized and official. The image of backland has been recognized, re understood and recognized in the historical changes in order to adapt to and deal with social and cultural beliefs and historical context. It creatively reforms and integrates the national historical and cultural traditions and the social practical experience of various times, and constructs a new cultural form that respects the tradition and reflects the social practical experience. Conclusions Nowadays, in the multicultural context, “Houtu belief”, as a new national custom and cultural event, not only ensures the cultural legitimacy of Houtu culture in the local society, but also continues the inseparable relationship and memory between them and their ancestral civilization. It provides a new theoretical perspective and practical basis for the later research in the multicultural context. It can also promote the use of psychology to broaden the direction of studying national customs and culture. Acknowledgement Supported by the following projects, 2019 Jinzhong University “1331 Project” innovation team “Shanxi Cultural Heritage Inheritance and Provincial Cultural Tourism Strengthen Provincial Strategy Research” (JzxycxTD2019002). 2020 Shanxi Philosophy and Social Science Research Project: Research on animal Images of Chinese Buddhist Art (2020W184). University-level teaching reform project of Jinzhong University: Research on teaching reform of “Intangible Cultural Heritage” into “Colleges and University Zhejiang Provincial Heritage Conservation Technology Project (2020016).